Tablet Splitting Performance Evaluation of Losartan Potassium and Olmesartan Medoxomil IR Tablets Marketed in Bangladesh (Bangladesh Pharmaceutical Journal, 2020)
Tablet splitting is a widely used practice in Bangladesh but there are no regulations for pharmaceutical companies to ensure that tablets are manufactured in such a way that facilitates appropriate splitting. Seven Losartan Potassium (LSP) brands and five Olmesartan Medoxomil (OLM) brands were selected and necessary number of tablets as well as a tablet splitter was collected. Weight variation, assay, invitro dissolution and loss of weight parameters were evaluated according to recent guidelines on the tablet fractions split by hand and by the splitter separately. Seven out of twelve brands displayed acceptable results in all parameter evaluations. EP and USP standards produced dissimilar results. In all assessments, machine-split portions produced better results than hand-split ones and so, a tablet splitter was found to be more reliable than using hands only. This study is preliminary in nature and thus further extensive studies are in progress involving more samples, more personnel and more laboratories as well as utilizing properly validated methodology and precisely calibrated instruments to get more conclusive data.Bangladesh Pharmaceutical Journal 23(2): 146-154, 2020